2015
DOI: 10.3892/etm.2015.2430
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation between Graves' disease and painless thyroiditis by diffusion-weighted imaging, thyroid iodine uptake, thyroid scintigraphy and serum parameters

Abstract: Abstract. The aim of the present study was to assess the apparent diffusion coefficient (ADC) in diffusion-weighted imaging (DWI), thyroid radioactive iodine uptake (RAIU), thyroid scintigraphy and thyrotropin receptor antibody (TRAb) levels in the differential diagnosis between Graves' disease (GD) and painless thyroiditis (PT). A total of 102 patients with GD and 37 patients with PT were enrolled in the study. DWI was obtained with a 3.0-T magnetic resonance scanner, and ADC values were calculated. RAIU and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…One study reported that the optimal threshold ADC value that was used to differentiate Graves’ disease from painless thyroiditis was 1.837×10 –3 mm 2 /sec, with sensitivity, specificity, accuracy, PPV, and NPV of 96.078, 91.892, 95.000, 97.059 and 89.474%, respectively [ 27 ]. Another study added that the ADC value was significantly higher in patients with Graves’ disease in comparison to patients with painless thyroiditis ( P = 0.05); the mean ADC values of the thyroid gland in Graves’ disease were 3.47, 2.25 and 1.64×10 –3 mm 2 /sec, and in Hashimoto thyroiditis they were 2.53, 1.76, 1.28×10 –3 mm 2 /sec for b -values of 100, 600, and 1000 sec/mm 2 , respectively.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…One study reported that the optimal threshold ADC value that was used to differentiate Graves’ disease from painless thyroiditis was 1.837×10 –3 mm 2 /sec, with sensitivity, specificity, accuracy, PPV, and NPV of 96.078, 91.892, 95.000, 97.059 and 89.474%, respectively [ 27 ]. Another study added that the ADC value was significantly higher in patients with Graves’ disease in comparison to patients with painless thyroiditis ( P = 0.05); the mean ADC values of the thyroid gland in Graves’ disease were 3.47, 2.25 and 1.64×10 –3 mm 2 /sec, and in Hashimoto thyroiditis they were 2.53, 1.76, 1.28×10 –3 mm 2 /sec for b -values of 100, 600, and 1000 sec/mm 2 , respectively.…”
Section: Discussionmentioning
confidence: 99%
“…This process is associated with a diffuse lymphocytic infiltration in the thyroid gland. Hypercellularity in painless thyroiditis leads to numerous structural components and membranes, resulting in greater impedance and restriction of diffusion of water molecules, which leads to lower ADC values [ 24 , 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[13][14][15] Unlike iodide however, pertechnetate after its trapping does not undergo organification. 2,16 Apart from the thyroid gland, NIS is also expressed on choroid plexus, salivary glands, gastric mucosa, lactating mammary glands and ciliary body of eyes. Technetium 99m pertechnetate is readily available from a Molybdenum-99/ Tc-99m generator which is usually available within all nuclear medicine departments.…”
Section: Figure 1 30-year-old Female Diagnosed With Hyperthyroidismmentioning
confidence: 99%